'Ons is saam' – Afrikaans metal and rebuilding whiteness in the Rainbow Nation. Issue 2 (1st June 2014) - Hoad, Catherine
The South African general election of 1994 installed a democratic system of government in a nation that had ruptured by violent segregation since 1948. While the 'miracle' of the Rainbow Nation aimed for a unified state, the redistribution of power heralded by the rise of 'new' South Africa left much of the white Afrikaner population with a sense of loss. The task of the post-apartheid Afrikaner cultural industry is now concerned with finding a place for the Afrikaner in modern South Africa. As such, this article explores how 'Afrikaans metal' has been compliant in fostering a sense of community and encourages sentiments of localized belonging. The passion and dynamism of heavy metal allows for the proliferation of a metal scene explicitly concerned with the promotion of an Afrikaner identity, performing in Afrikaans and creating Afrikaans metal for South African metal fans. However, just as the Afrikaner community at large struggles to find a white identity untarnished by apartheid, Afrikaans metal fans and bands face a similarly complex mission. Afrikaans metal represents a site within which this 'lost' Afrikaner identity can be both reclaimed and contested, and thus renegotiates the role of Africa's 'white tribe' into the twenty-first century.